Ekspansi Pasar Global Kejaya Handycraft: Strategi Pemasaran Sosial dalam Dakwah dan Pemasaran Produk Kerajinan Handmade - Mita, Imelda Nur (Fakultas Dakwah UIN KHAS Jember, 2024)
Globalization and advancements in information technology have created opportunities for small and medium enterprises to enter international markets, including the handmade craft sector. However, many entrepreneurs face challenges in developing effective global marketing strategies. Kejaya Handicraft has adopted a social marketing approach based on dakwah principles to expand its market reach. This study aims to analyze the effectiveness of social marketing and product marketing strategies in global expansion. This research employs a qualitative method with a case study approach. Data were collected through in-depth interviews, direct observations, and document analysis of Kejaya Handicraft’s marketing strategies. Thematic analysis was conducted to identify patterns in the application of dakwah values in marketing. The findings reveal that integrating dakwah values such as honesty, trustworthiness, and sustainability enhances brand image and consumer loyalty in international markets. Kejaya Handicraft successfully expanded its market through continuous innovation, strategic collaborations, and digital media utilization. In addition to improving business competitiveness, this strategy also contributes to local economic empowerment. This study underscores that dakwah-based social marketing can serve as an effective strategy in addressing globalization challenges and enhancing the competitiveness of handmade craft products in international markets.